Efektivitas Terapi Kombinasi Microneedling dan Vitamin C Terhadap Perbaikan Parameter Kulit Wajah - Tan, Sukmawati Tansil; Yogie, Giovanno Sebastian; Destra, Edwin; Afladhanti, Putri Mahirah; Sarijuwita, Alicia; Tamaro, Anggita (Jurnal Ners, 2024)
UV rays can affect various skin physiology, including changes in skin thickness and skin color. Vitamin C acts as an antioxidant to reduce melanin and skin damage caused by the sun, but it requires a combination with other therapies to get optimal results. This research focuses on the effectiveness of microneedling with vitamin C against pigmentation and skin damage due to sun exposure. The design of this research is quasi experimental. Patients who have atrophic acne scars who meet the inclusion criteria and are treated at Sukma Cliniq Tangerang are the population in this study. The intervention in this study was microneedling with a mixture of 10% vitamin C serum to improve the skin (given when the intervention was carried out and used at home for 21 days). The intervention will be carried out on day 0 according to the procedure previously explained and measured again on day 42. The variable measurements in this study aim at the value of UV damage and skin pigmentation before and after the combination therapy. Results: There were 36 respondents who met the inclusion criteria for this study with an average age of 33.03 years and 69.4% of respondents were women. There were changes and improvements in roughness, porphyrin, and pigmentation parameters (p value <0.001), but there was no change in UV damage parameters (p value 0.500) both before and after the intervention. There were changes and improvements in roughness, porphyrin, and pigmentation parameters after microneedling and vitamin C therapy before and after 42 days of therapy. However, there are no changes and improvements to the UV damage parameters.